(untitled) (Conference Zone, 2022)
The relationship of obesity and diabetes to liver disease (1) (obese-diabetic liver disease) was first reported over three decades ago. In 1980, Ludwig and his collaborators (2) described the condition of a series of patients, who without having a significant history of alcohol consumption, showed histopathological changes that were indistinguishable from those occurring in alcoholic liver disease. This group coined the term "non alcoholic steatohepatitis" (NASH), which has been recognized since then as one of most frequent liver diseases in the world (3). Its potential progression to cirrhosis (4), liver insufficiency (5) and hepatocellular carcinoma (6, 7) has been identified. The real importance of NASH in Colombia is unknown, but it is increasingly the reason for general consultations, and increasingly leads to cirrhosis and liver transplants.